Treatments for Female Victims of Intimate Partner Violence: Systematic Review and Meta-Analysis - Karakurt, Günnur; Koç, Esin; Katta, Pranaya; Jones, Nicole; Bolen, Shari D. (Frontiers in Psychology, 2022)
Intimate partner violence (IPV) is an important problem that has significant detrimental effects on the well-being of female victims. The chronic physical and psychological effects of intimate partner violence (IPV) are complex, long-lasting, chronic, and require treatments focusing on improving mental health issues, safety, and support. Various psycho-social intervention programs are being implemented to improve survivor well-being. However, little is known about the effectiveness of different treatments on IPV survivors' well-being. For this purpose, we conducted a systematic review and meta-analysis to assess the effectiveness of interventions on improving outcomes that describe the well-being of adult female survivors of IPV. We searched PubMed, PsycINFO, and Cochrane Library. We explored the effectiveness of available interventions on multiple outcomes that are critical for the well-being of adult female victims of IPV. To provide a broad and comprehensive view of survivors’ well-being, we considered outcomes including mental health, physical health, diminishing further violence, social support, safety, self-efficacy, and quality of life. We reviewed 2,770 citations. Among these 25 randomized-controlled-study with a total of 4683 participants met inclusion criteria. Findings of meta-analyses on interventions indicated promising results in improving anxiety [standardized mean difference (SMD) -7.15, 95% confidence interval (CI) -8.39 to – 5.92], depression (SMD -.26, CI -.56 to -.05), safety (SMD = .43, CI 04 to .83), violence prevention (SMD = -.92, CI -1.66 to -.17), health (SMD = .39, CI .12 to .66), self-esteem (SMD = 1.33, CI -.73 to 3.39), social support (SMD = .40, CI .20 to .61), and stress management (SMD = -8.94, CI -10.48 to -7.40) at the post-test. We found that empowerment plays a vital role, especially when treating depression and Post Traumatic Stress Disorder (PTSD), which are difficult to improve across interventions. We found mixed findings on self-efficacy and quality of life. The effects of IPV are long-lasting and require treatments targeting co-morbid issues including improving safety and mental health issues.